Advances in Information Retrieval 34th European Conference on IR Research, ECIR 2012, Barcelona, Spain, April 1-5, 2012. Proceedings - Baeza-Yates, Ricardo; Vries, Arjen P.; Zaragoza, Hugo.; Cambazoglu, B. Barla; Murdock, Vanessa; Lempel, Ronny; Silvestri, Fabrizio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the proeedings of the 34th European Conference on IR Research, ECIR 2012, held in Barcelona, Spain, in April 2012. The 37 full papers, 28 poster papers and 7 demonstrations presented in this volume were carefully reviewed and selected from 167 submissions. The contributions are organized in sections named: query representation; blogs and online-community search; semi-structured retrieval; evaluation; applications; retrieval models; image and video retrieval; text and content classification, categorisation, clustering; systems efficiency; industry track; and posters.
Keywords: Computer science; Database management; Data mining; Information storage and retrieval systems; Multimedia systems; Artificial intelligence; Computer Science; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery; Information Systems Applications (incl. Internet).; Multimedia Information Systems; Artificial Intelligence (incl. Robotics).